Selective Direct and Indirect Feedback on Grammatical Error Reduction - N. Navarro, Ana Louella; S. Caballo, John Harry; A. Ngo, Cristy Grace (International Journal on Integrated Education, 2023)
The purpose of this study was to compare two feedback strategies - Selective Direct Feedback (SDF) and Selective Indirect Feedback (SIF) - in reducing grammatical errors in the writing of senior high school Humanities and Social Science students. The participants were 120 senior high school Humanities and Social Science students whose essays were evaluated for grammatical errors before and after receiving SDF and SIF from their teacher. The results showed that both SDF and SIF led to a significant decrease in grammatical errors in the students' writing. However, the reductions in errors were not significantly different between the two feedback methods.